Do highly exclusive social welfare programs increase political inequality? A comparative analysis of the 50 US states - Eric Plutzer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
In this paper, I empirically test the notion that the degree of inclusion/exclusion of social welfare policies can have important feedback effects on political participation of poor citizens. I conduct a comparative analysis of the 50 US states, using the uptake (or coverage rate) of the Food Stamp program as an indicator of relative inclusiveness. If the inclusiveness of the program sends a message to potential recipients about their worth in the community, these messages may encourage or discourage participation. Using data from the National Education Longitudinal Survey, 1988-2000, I show that the turnout of young citizens raised in poor families is dramatically influenced by the inclusiveness of the state's Food Stamp program. High inclusive states displayed much lower rates of political inequality. The mechanisms underlying this effect remain to be specified. However, in the context of previous individual-level studies, the results bolster the idea of policy feedback generally, and its impact on political inequality in particular.
Keywords: 300; Sozialpolitik; Soziale Sicherung; Soziale Ungleichheit; Wohlfahrtseffekt; Vergleich; USA; Deutschland